Industrial Packaging Management in the Circular Economy Model - Paták, Michal; Hromadníková, Kateřina; Branská, Lenka; Kocmanová, Alena (Česká společnost průmyslové chemie, 2022)
Introducing circular economy principles into a company's packaging management is one possible way to reduce the environmental impact of excessive use of packaging materials in industry, but also an opportunity to reduce the costs associated with packaging logistics. The aim of this paper is to identify the main opportunities and barriers for the management of industrial packaging according to the circular economy model based on qualitative research in a selected company in the chemical industry. The research was conducted through in-depth interviews with four managers of the company who are involved in the packaging management of the selected company. The research results provide examples of good practice while highlighting the main issues related to industrial packaging management in the areas of: sustainable material design, material savings, packaging reuse and packaging waste recycling.
Nakládání s průmyslovými obaly v modelu cirkulární ekonomiky
Keywords: circular economy; packaging; packaging management; sustainable packaging; waste management; cirkulární ekonomika; obal; obalové hospodářství; udržitelný obal; odpadové hospodářství